Implementasi Asas-Asas Umum Pemerintahan Yang Baik Pada Pemerintahan Kabupaten Dompu - Khalid Prawiranegara (Universitas Islam Indonesia, 2021)
The purpose of this study is to determine the implementation of the General Principles of Good Governance (AAUPB) in the Dompu Regency government and to examine the inhibiting factors in implementing AAUPB in the Dompu Regency government. This research is normative, the approach taken includes a statutory approach. The data collected were analyzed descriptively qualitatively. The results of the study conclude that, first, the administration of the Dompu Regency Government has implemented AAUPB as a guideline in the preparation of licensing policies in Dompu Regency, as stated in the Regent's Regulation Number 140 of 2010 concerning the Implementation of Environmental Document Services. Second, the inhibiting factor in the administration of the Dompu Regency Government is the quality factor of the human resources of the State Civil Apparatus in particular, namely the lack of understanding of technology.Key Words: Dompu regency government; general principles of good governanceAbstrakTujuan penelitian ini adalah untuk mengetahui implementasi Asas-Asas Umum Pemerintahan yang Baik (AAUPB) pada pemerintahan Kabupaten Dompu dan mengkaji faktor penghambat dalam menerapkan AAUPB pada pemerintahan Kabupaten Dompu. Penelitian ini bersifat normatif, pendekatan yang dilakukan meliputi pendekatan perundang-undangan. Data yang terkumpul dianalisis secara deskriptif kualitatif. Hasil penelitian menyimpulkan bahwa, pertama, penyelenggaraan Pemerintahan Kabupaten Dompu telah menerapkan AAUPB sebagai pedoman dalam penyusunan kebijakan perizinan di Kabupaten Dompu, dituangkan dalam Peraturan Bupati Nomor 140 Tahun 2010 tentang Penyelenggaraan Pelayanan Dokumen Lingkungan. Kedua, faktor penghambat dalam penyelenggaraan Pemerintahan Kabupaten Dompu adalah faktor kualitas sumber daya manusia Aparatus Sipil Negara secara lebih khusus yakni kurangnya pemahaman teknologi.Kata Kunci: Asas-asas umum pemerintahan yang baik; pemerintahan kabupaten Dompu